Tingkat Kesulitan Keuangan, Peluang Pertumbuhan, dan Insentif Pajak: Implikasinya pada Konservatisme Akuntansi - Nugraha, Erdy Yanuar Setya; Cahyaningtyas, Fadilla (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2025)
The purpose of this study is to determine whether the level of financial difficulty, growth opportunities, and tax incentives in technology subsector manufacturing companies listed on the IDX for the 2021-2023 period have an impact on accounting conservatism. This research uses a quantitative approach with purposive sampling technique. Secondary data was collected from the IDX website using documentation techniques. Multiple linear regression analysis is the analysis technique used. The research findings show that the level of financial distress and tax incentives have an impact on accounting conservatism, but growth opportunities have no impact on accounting conservatism.